A goal programming model for sustainable reverse logistics operations planning and an application. (10th November 2018) - Bal, Alperen; Satoglu, Sule Itir
Abstract: Global concerns about climate change and its environmental consequences, social factors and economic constraints require pursuit of a new approach to the supply chain planning at the strategic, tactical and operational levels. Recovery of waste electric and electronic equipment (WEEE) has become an important issue in the developing economies, as legislations that mandate manufacturers and importers to take back the wastes of their electrical and electronic products (WEEE) has been promulgated. Therefore, this study addresses the process of collecting WEEE products from service points, transporting them to recycling facilities, and recovery of the waste materials. Our framework considers triple-bottom-line approach and employs goal programming to reach economic, social and environmental targets. A multi-facility, multi-product and multi-period mathematical model is proposed, considering the real conditions, for the first time in the literature. In addition, this goal programming approach is illustrated on a WEEE reverse supply chain of the household appliances. Highlights: Operations planning of waste electrical electronic equipment logistics and recovery are considered. A triple-bottom line approach of sustainability is followed. A multi-facility, multi-product and multi-period goal programming model is proposed. Legal, environmental, economic and social objectives are considered. A real application of a reverse logistics and recovery operations of house-hold appliances is explained.